2021
DOI: 10.3390/ijms222212383
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions Associated with Fusarium Wilt Resistance in Flax

Abstract: Modern flax cultivars are susceptible to many diseases; arguably, the most economically damaging of these is the Fusarium wilt fungal disease. Over the past decades international flax breeding initiatives resulted in the development of resistant cultivars. However, much remains to be learned about the mechanisms of resistance to Fusarium infection in flax. As a first step to uncover the genetic factors associated with resistance to Fusarium wilt disease, we performed a genome-wide association study (GWAS) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Previous research [12] has highlighted the significance of cytochromerelated genes in plant defense. Also, earlier we reported QTN in a gene encoding flax' cytochtrome P450 protein associated with resistance to Fusarium infection [13]. Our findings further emphasize the indispensable role the cytochrome superfamily in plant pathogen response.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research [12] has highlighted the significance of cytochromerelated genes in plant defense. Also, earlier we reported QTN in a gene encoding flax' cytochtrome P450 protein associated with resistance to Fusarium infection [13]. Our findings further emphasize the indispensable role the cytochrome superfamily in plant pathogen response.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, Fusarium oxysporum f. sp. lini is one of the major flax pathogens affecting the world's crop production [ 48 ]. Whether the increase of CAP content in soil will inhibit the decrease of Fusarium pathogens needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the mapping was performed using mostly amplified fragment length polymorphism (AFLP) markers and the location of the QTLs on linkage groups 6 and 10 cannot be assigned to the pseudomolecules of the flax reference genome assembly (You et al 2018 ). Recently, Kanapin et al ( 2021 ) performed a genome-wide association study (GWAS) with nearly 300 accessions and identified one major locus for Fusarium wilt resistance in flax on chromosome 1 and minor loci on chromosomes 8, 11 and 13. The major chromosome 1 locus comprised ten quantitative trait nucleotides (QTNs), spanned 640 Kb and explained 7–10% of the phenotypic variance for Fusarium wilt resistance in their diversity panel.…”
Section: Introductionmentioning
confidence: 99%